Early contours of Philippine foreign policy under Ferdinand Marcos Jr.: Like father, like son - Felix Heiduk; Tom Wilms (Stiftung Wissenschaft und Politik (SWP), 2022)
Ferdinand "Bongbong" Marcos Jr. won the Philippines' presidential election by a landslide on 9 May and was officially sworn in on 30 June. During the election campaign, Marcos Jr. - the son of Philippine dictator Ferdinand Marcos Sr. who was ousted in 1986 - remained extremely vague when it came to describing his foreign and security policies. Some observers initially speculated that Marcos Jr. would continue to pursue the foreign policy shift towards the People's Republic of China that had been established by his predecessor Rodrigo Duterte. Several weeks into Marcos Jr.'s presidency, however, a much more nuanced picture has emerged. It appears that the newly elected president is likely seeking to balance the Philippines' relations with China and the US to a greater extent than his predecessor. He therefore seems to be following in his father's foreign policy footsteps. This could open up new opportunities for cooperation between the Philippines and Germany and the EU - provided that such collaboration considers the high degree to which Manila's current foreign policy agenda seems to be driven by domestic concerns and objectives.
urn:nbn:de:101:1-2022102613362982496564
Keywords: 320; Philippine; foreign policy; presidential elections; Ferdinand Marcos Jr.; Rodrigo Duterte; Southeast Asia; Indo-Pacific; China; US; EU